The influence of Helium-Neon laser irradiation on wound healing - RABAB HAJWAL AL-ZAMILY (International Journal of Pharma and Bio Sciences, 2018)
Low level laser is commonly applied in repair of tissues. Tissue healing is a complex process, which; involving’. Local and systemic responses. The aim of this study is to compare the effect of two different helium-neon (He-Ne) laser irradiation energies on superficial wounds. The second was the effect of He-Ne irradiation on superficial and deep wounds. Seventy young male rats were used in this study. They were divided into four groups. A superficial wound of the first and the second groups were irradiated by He-Ne laser using the flowing energies 0.153, 0.3 Joule for 3, and 6 min respectively. The third group with superficial wound, not irradiated, was regarded as a control group. The fourth group, with a deep wound, was irradiated only by the first energy. A biopsy was taken from all rats for histological examination at 1, 3, and 7 days post-operative. The results revealed clear healing of superficial and deeper wounds in the irradiated groups than control. The best healing was found in the treated group by energy of 0.153 joules for 3 minutes, and failure healing very deep wounds.